THE RELATION OF BUSINESS ORGANIZATION TO ACCOUNTING. - Noble, Howard S. (The Accounting Review, 1927)
Abstract It has been seen, especially in the U.S., that for any given industry an increasing or decreasing of accounting structure parallels a similar increase or decrease in the organization. Business organization and administration tend to place emphasis upon the personal elements in business activity. Personal element, that is, recognition of the parts played by individuals within their business units, is a factor which makes vital the accounting records. Business organization expresses the relationships of owners among themselves and to operators or managers engaged in the service of the owners. A second form of relationship is found in what Is sometimes called "internal organization," organization in terms of the various functions performed by the individuals or by groups of Individuals within the business unit. In the article, a brief consideration of two types of organization relationships between the element of business organization and administration and accounting have been discussed, which include, firstly, the work of the auditor in certification, and secondly, the recent development of the operating statement for purposes of administrative control.